Authigenic carbonate precipitation at Yam Seep controlled by continuous fracturing and uplifting of four-way closure ridge offshore SW Taiwan - Tseng, Yiting; Smrzka, Daniel; Lin, Saulwood; Schröder-Ritzrau, Andrea; Frank, Norbert; Bohrmann, Gerhard (Geochemistry, geophysics, geosystems, 2023)
Hydrocarbon seeps are common manifestations of gas leakage from the seafloor. However, the fate of methane seepage within the gas hydrate stability zone at active margins is poorly constrained. This study presents a 40-thousand-year record of hydrocarbon seepage archived by a ∼5-m long core composed of authigenic carbonate from the Yam Seep area, Four-Way Closure Ridge off SW Taiwan. Different carbonate microfacies could be distinguished: Consolidated microcrystalline aragonite representing lithified host sediments intercalated by pure aragonite present in 10-50 cm thick intervals in the core. These aragonite intervals are interpreted as having precipitated within former fractures in the host rock. High resolution U-Th dating of these aragonites is interpreted to record the minimum age of the opening of these fractures. The chronology of aragonite precipitation throughout the core suggests a record of continuous seepage from ∼41 to 2 ka that fluctuated in intensity over this time period. The chronology of putative fracturing events and observed carbonate precipitation suggest (a) an active period of fracturing and seepage from ∼37 to 27 ka, (b) a more quiescent period from ∼27 to 16 ka, followed by (c) another active period from ∼16 to 12 ka. A schematic model illustrates the evolution of carbonate formation within the core influenced by faulting, fracturing, erosion, gas hydrate accumulation, and aragonite precipitation and provides a unique 40,000-year-old record of methane seepage and crucial insights into the dynamics of long-term seepage systems at active margins.